2012
DOI: 10.1002/jez.b.22481
|View full text |Cite
|
Sign up to set email alerts
|

Dicer‐Processed Small RNAs: Rules and Exceptions

Abstract: Canonical microRNAs are excised from their hairpin-shaped precursors by Dicer. In order to find possible exceptions to this rule and to identify additional substrates for Dicer processing we re-evaluate the small RNA sequencing data of the Dicer knockdown experiment in MCF-7 cells orignally published by Friedländer et al. [Nucleic Acids Res. 40: 37-52 (2012)]. While the well-known non-Dicer mir-451 is not sufficiently expressed in these experiments, there are several additional Dicer-independent microRNAs, amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 67 publications
2
45
0
Order By: Relevance
“…Especially efficient was Dicer-1 depletion for candidate discrimination, as this approach allowed discarding 2,117 out of the 2,675 candidates in a first filter, results that are in concordance with those of other authors252627. It is worth noting, however, that Dicer-1 depletion did not significantly affect 10% of the conserved miRNA, which might be Dicer-1 independent miRNAs28.…”
Section: Discussionsupporting
confidence: 78%
“…Especially efficient was Dicer-1 depletion for candidate discrimination, as this approach allowed discarding 2,117 out of the 2,675 candidates in a first filter, results that are in concordance with those of other authors252627. It is worth noting, however, that Dicer-1 depletion did not significantly affect 10% of the conserved miRNA, which might be Dicer-1 independent miRNAs28.…”
Section: Discussionsupporting
confidence: 78%
“…Different classes of probes can receive different weights depending on their reliability as invariant controls. Affymetrix miRNA microarrays contain about one-fifth of non-miRNA small RNA probes (small nucleolar RNAssnoRNAs-comprising small Cajal body-specific RNAs, and C/D box and H/ACA box small RNAs), which are mostly independent of the miRNA processing pathway (Langenberger et al 2013). We postulated that such non-miRNA probes from the Affymetrix platform could be used as invariant probes for cyclic loess.…”
Section: Normexp Background Correction With Cyclic Loess Normalizationmentioning
confidence: 99%
“…5 F ). Conversely, others and we have shown that there is at least 2-fold decrease of miR-21 in the Dicer −/− HCT116 cells [34], [44]. The data indicate that the expression of the SNORD44 sdRNAs is independent of the canonical miRNA-processing pathway.…”
Section: Resultsmentioning
confidence: 47%
“…Dicer has been implicated in the processing of H/ACA snoRNA [30] but not box C/D snoRNAs [44]. We hence explored the possibility that the miRNA pathway is involved in the processing of the SNORD44-derived fragments.…”
Section: Resultsmentioning
confidence: 99%